Verity : in tune with viral marketing - Krost, Peta; Saini, Yvonne ([London] : SAGE, 2016)
Looking across the bay from her home in Hout Bay, Cape Town singer Verity Price (known to her fans as Verity) reflected on how she had not allowed the exclusive South African music industry to prevent her from making and selling her first album. She was one of the world forerunners in using Internet viral marketing to sell her music, and she was the first singer to sell an album before it had been made. Now, in April 2009 - nine months after her album was launched - sales had slowed, and she wondered whether she could use viral marketing differently to increase sales?
Originally Published in: Krost Maunder, P. & Saini, Y. (2009). Verity: In Tune with Viral Marketing. WBS-2009-16. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Verity; Direct marketing -- Case studies; Online social networks in business -- Case studies